Causes of death in patients with chronic sarcoidosis - Hu, Xiaowen; Carmona, Eva M.; Yi, Eunhee S.; Pellikka, Patricia A.; Ryu, Jay (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Introduction: Sarcoidosis is a multi-system, granulomatous disorder of unknown etiology that is associated with a variable prognosis and sometimes results in death. There are conflicting reports regarding the causes of death in patients with sarcoidosis. Methods: Forty-four consecutive patients with sarcoidosis who underwent an autopsy (35 patients) or died at Mayo Clinic (Rochester, MN, USA) over a 20-yr period, from January 1, 1994 to December 31, 2013 were analyzed. Results: The median age at death was 63 years (range, 33-94 years) and there were 22 (50%) women. Sarcoidosis had not been clinically diagnosed in 16 (36%) patients before death. Fifteen deaths (34%) were related to sarcoidosis and included seven deaths (16%) from cardiac sarcoidosis and four deaths (9%) from progressive pulmonary sarcoidosis. Other sarcoidosis-related causes of death included advanced hepatic sarcoidosis (5%) and opportunistic infections (5%) related to immunosuppressive therapy for treating sarcoidosis. Among seven patients dying from cardiac sarcoidosis, three had been diagnosed with sarcoidosis during life and cardiac involvement was known in two of them. Six of seven deaths from cardiac sarcoidosis occurred in the autopsied cohort while all four deaths from pulmonary sarcoidosis occurred in those not autopsied. Conclusions: In the majority of patients dying with sarcoidosis the cause of death is unrelated to sarcoidosis. Cardiac involvement is the most common cause of sarcoidosis-related deaths in patients subjected to postmortem examination and was usually undiagnosed during life. The cause distribution of death in patients with sarcoidosis differed depending on whether autopsy was performed.